Phytochemical, Pharmacological, and Toxicological Prospection of Morus nigra L.: A Systematic Review - Alves, Larissa P.; dos Santos, Widson Michael; de Souza, Myla Lôbo; Rolim, Larissa Araújo; Rolim-Neto, Pedro José (Natural Products Journal, The, 2024)
Introduction: Morus nigra L. has industrial relevance due to the presence of specialized metabolites, which possess pharmaceutical potential in various parts and preparations. This review presents updated information on traditional, phytochemical, and pharmacological applications, as well as toxicity data, pertaining to different parts of Morus nigra L. Method: Phytochemical research and ethnobotanical studies were conducted using reviewed databases. Mulberry leaves have demonstrated several biological activities, attributed to the presence of phenolic acids, flavonoids, and fatty acids. Stems and roots contain additional compounds such as stilbenes and benzofurans. Morus nigra L. exhibits various biological activities, including hepatoprotective, hypolipidemic, anti-inflammatory, antioxidant, antimicrobial, neuroprotective, hypoglycemic, skin whitening, cytotoxic, antiatherosclerotic, and antiobesity effects. The choice of extraction technique and plant part is crucial to obtain a diverse range of compounds necessary for specific indications. Result: Accelerated solvent extraction (ASE) has proven to be the most advantageous method compared to supercritical fluid maceration and extraction (SFE), yielding a wide variety of compounds. Conclusion: Overall, this review aims to provide scientists and companies interested in Morus nigra L. with opportunities and challenges for innovation in this field.
Keywords: extraction process